Analisis Jalur Pengadaan Material Dan Anggaran Pada Ketepatan Waktu Pelaksanaan Proyek Pembangunan Jalan Tol Kunciran-Batuceper-Cengkareng Terhadap Kinerja Proyek - Chamsudi, Danie Hayam Mada; Suryobuwono, Abdullah Ade; Situmorang, Johan Kiara; Antonius, Sulistiyono; Firmansyah, Iqbal; Parlindungan, Purbanuara (Jurnal Sistem Transportasi & Logistik, 2022)
The purpose of this study is to examine the correlation between material procurement and project budget, the influence of project budget on punctuality, the influence of project budget on performance, the influence of material procurement on timeliness, the influence of material procurement on performance and the effect of punctuality on performance on the implementation of the toll road construction project. This research method is a method of path analysis research. The results of this study concluded that the Budget for performance control, success compensation and work benchmarks that have good value, then affect the timeliness and performance of the project. Procurement of materials that have good speed, capability, and reliability, affects the timeliness and performance of projects on the ground. Timeliness on the budget and project material affects the performance on the ground in the process of toll road construction activities. If budget value, material procurement and punctuality have good value to project performance, then project performance has quality, quantity and efficiency in project execution.